UNDERSTANDING LEARNING EXPERIENCES AND MAJOR MISMATCH AMONG INFORMATICS STUDENTS - Luh Gede Surya Kartika; I Putu Adi Saskara; Gede Wahyu Sanjaya; Putu Kussa Laksana Utama (International Journal of Social Studies, 2025)
This study investigates the academic experiences, perceptions, and practical skill development of first- and second-year students in the Informatics Study Program at UHN I Gusti Bagus Sugriwa Denpasar. As a newly established program with students from diverse educational backgrounds, several challenges have emerged, including perceptions of being in the “wrong major,” dissatisfaction with learning facilities, and difficulties in mastering technical content. The research employs a descriptive quantitative design involving all 66 active students in 2024, of whom 47 provided valid responses to an online survey. The instrument consisted of open-ended questions covering motivations for choosing the major, learning materials, practical skills, satisfaction with campus facilities and lecturers, general complaints, and perceptions of academic misalignment. Data were analyzed using topic classification and frequency analysis, allowing identification of dominant themes associated with student satisfaction and dissatisfaction. The findings show that the primary source of “wrong major” perceptions is the difficulty of understanding technical subjects such as programming, algorithmic logic, and computational mathematics. Students also reported a mismatch between initial expectations and the actual curriculum, which emphasizes computational problem-solving rather than basic computer operations. General complaints centered on inadequate laboratory facilities, limited practicum opportunities, and inconsistent pedagogical support. Despite these issues, many students expressed satisfaction with improvements in their coding and problem-solving abilities, reflecting the benefits of the program’s computational thinking–based approach. The study concludes that strengthening digital infrastructure, expanding practice-based learning, and improving academic support systems are essential to enhancing student satisfaction and reducing academic misalignment in the early years of the program.